ON TIME PERFORMANCE IN THE AIRLINE INDUSTRY AS THE IMPACT OF FLIGHT FREQUENCY AND FLIGHT DELAY - Edhie Budi Setiawan; Intan Pawreski; Datonabolon Datonabolon; Lira Agusinta; Theresye Yoanyta Octora (Universitas Gorontalo, 2021)
Every airline is always competing in providing the best service for passengers. They compete to prevent delays and maintain punctuality, as well as regulate flight frequency. The purpose of this study was to determine the effect of flight frequency on flight delays and its impact on the on time performance of PT. Garuda Indonesia. The data used are secondary data for 35 months (35 data) and processed using Structural Equation Modeling (SEM) PLS analysis. The results of the analysis and discussion show that flight frequency has a significant positive effect on flight delay, while flight delay has a significant negative effect on on time performance and flight frequency also has a significant negative effect on on time performance, as an indirect effect of flight frequency on on time performance through flight delay. To maintain on time performance, airlines must be able to reduce flight delays.